Effectiveness of buprofezin against mealybug (Phenacoccus solenopsis) and predatory complex in Bt cotton - DHAWAN, A K; SHERA, P S; ANEJA, ANAND; KUMAR, VIJAY; BHULLAR, H S (The Indian Journal of Agricultural Sciences, 2014)
IGR Buprofezin 25 SC (Applaud) was tested at three dosages, viz 187.5, 250 and 312.5 g a.i./ha against mealybug, P. solenopsis on Bt cotton in 13 different experiments during 2007 and 2008 at farmers’ field in Bathinda, Mansa, Muktsar, Faridkot, Ludhiana and Ferozepur districts along with profenophos and thiodicarb as standard checks and untreated control. Buprofezin (312.5 g a.i./ha) was found to be at par with thiodicarb 7 and 10 DAS but inferior than profenophos. However, all the three tested buprofezin dosages were significantly inferior as compared to profenophos and thiodicarb 3 DAS. Buprofezin was found to be safe to predatory complex when compared to profenophos and thiodicarb. Therefore, when the insecticides are needed for management of mealybug, buprofezin may be preferred to other available conventional insecticides as first spray as insecticide selectivity is crucial to conserve natural enemies.